KONSERVASI NILAI PANCASILA SEBAGAI LANDASAN DASAR PENGEMBANGAN KARAKTER MAHASISWA PGSD UNNES DALAM BERBANGSA DAN BERNEGARA - Hidayah, Eva Nur; Agnes Layung Sari, Dyta; Khotimah, Khusnul; Harahab, Rizky Dinda Sarmita; Permatasari, Mitra; Akbar Hajuan, Muhammad (Kajian Moral dan Kewarganegaraan, 2025)
Pancasila as the basic ideology of the Indonesian nation has an important role in shaping student character. The conservation of Pancasila values is pursued in Elementary School Teacher Education (PGSD) as one of the study programs at Semarang State University (UNNES) which is a conservation-minded university. This research aims to analyze and explore the strategy of Pancasila value conservation that is internalized among PGSD UNNES students as the basis for character development in the life of the nation and state. This research uses a qualitative descriptive approach conducted in the PGSD UNNES study program. Data collection methods in this study are interviews, documentation, and observation. The research subjects were students, lecturers, and campus leaders. The data analysis technique used is an interactive model with the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the Pancasila value conservation strategy in the PGSD UNNES Study Program proved effective in shaping student character holistically. The strategy includes value assessment through reflective discussions and scientific activities; active learning through compulsory courses based on Pancasila values; implementation through student involvement in Tri Dharma activities; and actualization in campus culture and student organization activities. These four aspects form an integrated and sustainable character education ecosystem. Students show improvement in social awareness, concern for the environment, tolerance for diversity, and the ability to practice the noble values of Pancasila in everyday life. In addition, active involvement in social and cultural activities is an indicator of the success of value internalization. However, the implementation of this conservation faces challenges in the form of the influence of globalization, inconsistency of role models, and limited space for actualization. Nevertheless, the conservation of Pancasila values remains relevant and significant as the foundation of character building for future educators.